2009
DOI: 10.1111/j.1523-5378.2009.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin–Amoxycillin‐Containing Triple Therapy: A Valid Empirical First‐Line Treatment for Helicobacter pylori Eradication in Hong Kong?

Abstract: The standard 7-day clarithromycin-containing triple therapy is still valid as the most effective empirical first-line eradication therapy for H. pylori infection in Hong Kong, as prevalence of primary resistance of H. pylori to amoxycillin and clarithromycin remains low. Patients who failed their empirical first-line eradication therapy should undergo H. pylori susceptibility testing to guide further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…These results are similar to those observed in the works of Bellelis [20], and Coelho [22] in research studies also conducted in Brazil. Results in works from Taiwan [23], Kuwait [24], Hong Kong [25], Iran [26], and Chile [27] have presented similar results regarding the efficacy of triple therapy. Metaanalysis of published works regarding the differences between the PPI in H. pylori treatment regimens showed eradication rates between 82% and 84% when they were combined with amoxicillin and clarithromycin [15,16].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These results are similar to those observed in the works of Bellelis [20], and Coelho [22] in research studies also conducted in Brazil. Results in works from Taiwan [23], Kuwait [24], Hong Kong [25], Iran [26], and Chile [27] have presented similar results regarding the efficacy of triple therapy. Metaanalysis of published works regarding the differences between the PPI in H. pylori treatment regimens showed eradication rates between 82% and 84% when they were combined with amoxicillin and clarithromycin [15,16].…”
Section: Discussionsupporting
confidence: 66%
“…Second-and third-generation macrolides have been commercially available for a long time, but they are not used widely due to their elevated cost, a fact which may suffice to explain these low resistance rates in our country. Conversely, the widespread use of nitroimidazolic compounds to treat parasitic infections, sexually transmitted diseases, and gynecological infections might be responsible for the significant reduction in H. pylori metronidazole sensitivity as several authors have observed [11,12,25,[36][37][38][39]41].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the flow diagram of the process by which articles were selected. Finally, 13 RCTs met our predefined inclusion and exclusion criteria and were qualified for the meta-analysis [8][9], [11][21]. From 13 RCTs, two of them [16], [20] were excluded because of their Jadad score was <3, three of them [8], [11], [14], compared 10 days of levofloxacin based regimen to 10 days of standard therapy, and the study by Zullo et al [21] was excluded because the standard arm was unique and contained 7 days of Clarithromycin, Tinidazole, Bovine Lactoferrin and Rabeprazole.…”
Section: Resultsmentioning
confidence: 99%
“…However, the eradication rates achieved with first-line levofloxacin-based treatments are not uniform. Some reports show improved efficacy with levofloxacin-based regimens in comparison to standard first-line therapy, whereas others have found equivalent or poorer responses [9], [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The start date of the prescriptions should be the same, with an overlapping duration of 7–14 days. Clarithromycin-based triple therapy was the first-line therapy for H. pylori in Hong Kong during the study period due to the low clarithromycin resistance rate (8%)23 and overall high eradication rate (>90%) 24. To remove the confounding effects of symptoms from gastric cancer leading to the use of PPIs or histamine 2-receptor antagonist (H2RA) (ie, protopathic bias), prescriptions of these agents started within 6 months prior to the gastric cancer diagnosis were excluded 25 26…”
Section: Methodsmentioning
confidence: 99%